Reduce the Bad Impact of Gadgets in Social Interaction with the Provision of Guidance Services in Discussion Technique Group to Students in Class IX Mts Al Bukhari Labuhanbatu - Efira Andiyani Batubara; Monica Mulyani Batubara; Apriliana Apriliana; Nora Adi Anna Harahap; M.Yusril Fuad (Universitas Muhammadiyah Enrekang, 2023)
The problem in this study is whether the provision of discussion group guidance services can reduce the negative impact of gadgets on social interaction of Class IX students of MTs Al Bukhari Labuhanbatu T.A. 2022/2023. To obtain data in this study, researchers collected data through observation and questionnaires. This type of research is Classroom Action Research (CAR), which consists of 2 cycles, cycle I and cycle II, each of which has 2 meetings. In each cycle the researcher conducts an immediate assessment (Laiseg) and distributes a questionnaire. The purpose of this study was to reduce the negative effects of gadgets in social interaction through group discussion technique guidance services for Class IX students of MTs Al Bukhari Labuhanbatu T.A. 2022/2023. Based on the results of the questionnaire analysis before being given action, 12 students were obtained with 9 people having the lowest social interaction due to the influence of gadgets and 3 people having the highest social interaction. so that the initial percentage in 1 group is 25%. From the results of data analysis in cycle I, after being given the action, it was found that 3 students experienced an increase in social attitudes so that the percentage of success became 50%, this can be seen from the results of the questionnaire and segment analysis. In cycle II there was a significant increase in students' social interaction, namely 83% because it was obtained 4 students who experienced an increase. Even though there are still 2 students (17%) who are categorized as 'moderate', the service success rate has met the target of 75%. Thus it can be concluded that the adverse effects of using gadgets in student social interaction can be reduced through group discussion technique guidance services for Class IX MTs Al Bukhari Labuhanbatu T.A. 2022/2023. It is recommended that this discussion technique group guidance service be used by counseling teachers at MTs Al Bukhari Labuhanbatu in order to reduce the negative impact of gadgets on students' social interactions at school